Formulasi Strategi Manajemen Risiko untuk Meningkatkan Stabilitas Operasional Perbankan Syariah di Indonesia - Albi Wahyu Ramadhan; Muhammad Munawwirul Hayat; Zultoni Lubis; Devita Azwi Nurahma; Dwi Artika Urbasari (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
Islamic banking in Indonesia has shown positive growth; however, it continues to face various risks that may affect operational stability. The distinctive characteristics of Islamic banking, which are based on profit-sharing principles and Sharia compliance, require the implementation of comprehensive and integrated risk management. This study aims to formulate risk management strategies to enhance the operational stability of Islamic banking in Indonesia. The research employs a qualitative descriptive approach through a literature review of academic books, scholarly journal articles, and official reports and regulations issued by the Financial Services Authority, Bank Indonesia, and related institutions. The findings indicate that financing risk, liquidity risk, operational risk, and Sharia compliance risk are the main risks influencing the operational stability of Islamic banks, with financing risk being the most dominant. The implementation of integrated risk management aligned with good corporate governance, effective Sharia supervision, human resource development, and the utilization of information technology plays a crucial role in strengthening operational stability. This study highlights that risk management functions not only as a control mechanism but also as a strategic instrument in supporting the sustainability of Islamic banking in Indonesia.